Serum markers of the extracellular matrix remodeling reflect antifibrotic therapy in bile-duct ligated rats - Schierwagen, Robert; Klein, Sabine; Leeming, Diana J.; Granzow, Michaela; Nielsen, Mette J.; Sauerbruch, Tilman; Krag, Aleksander; Karlsdal, Morten A.; Trebicka, Jonel (Frontiers in Physiology, 2013)
Background Progression of liver fibrosis is characterized by synthesis and degradation of extracellular matrix (ECM). Matrix-metalloproteinases (MMP) cleave collagen fibers at a specific site and thereby generate soluble fragments of ECM (neo-epitopes). The levels of these neo-epitopes might reflect the stage of liver fibrosis and may allow monitoring of anti-fibrotic therapies. Here we analyzed these neo-epitopes as read-out for a liver directed therapy with statins. Methods Bile duct ligation (BDL) was performed on wildtype rats, which received atorvastatin (15mg/kg*d) for one week starting at one, two, three, four and five weeks after BDL (T1-T5), while controls remained untreated. Hepatic fibrosis was analyzed by immunohistochemistry and hepatic hydroxyproline content. TGFβ levels were measured by RT-PCR. Proteolytic activity of MMP-2 was examined by zymography. Levels of degradation MMP driven type I, III, IV and VI collagen degradation (C1M, C3M, C4M and C6M) and type III and IV collagen formation (PRO-C3 and P4NP7S) markers were assessed by specific ELISAs in serum probes. Results Serum markers of ECM neo-epitopes reflected significantly the deposition of ECM in the liver and were able to distinguish between early (T1-T3) and severe fibrosis (T4-T5). Statin treatment to the fibrotic livers resulted in reduction of neo-epitope markers, especially when therapy was started in the stage of severe fibrosis (T4-T5). Furthermore, these markers correlated with hepatic expression of profibrotic cytokines TGFβ1 and TGFβ2. Formation markers of type III and IV collagen (PRO-C3 and P4NP7S) and degradation markers C4M and C6M correlated significantly with MMP-2 activity in rats with severe fibrosis. Conclusion Determination of ECM remodelling turnover markers in serum allowed a distinction between mild and severe fibrosis. With respect to statin therapy, the markers may serve as read-out for efficacy of anti-fibrotic treatment.